IDENTIFYING VOCABULARY MASTERY PROBLEMS DURING ONLINE LEARNING AT THE SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Soraya Khumaira; Mardiana Mardiana; Nur Aliyah Nur (International Conference on Social and Islamic Studies, 2021)
The results of this research are expected to give information about the students’ problems in mastering vocabulary and the effect on the students’speaking activity. The research design used was case study with qualitative descriptive design. It was conducted at the second semester of English Education Department at UIN Alauddin Makassar in academic year 2021. There were 5 students pointed as the participants of this research; they are from PBI-C. Theresearcher used interview guideline to collect the data. The data were analyzed using content analysis such as data condensation, data display, conclusion drawing and verification. The result of this research showed that the students nearly had similar problems in mastering vocabulary. They found it difficult to understand the meaning of vocabulary because there were some of them that have similar sound one another. Furthermore, the particular rules and types of nounmade the students confused when putting them into sentences while speaking. They often misplaced and got wrong grammar when they spoke. The students also have problems when they talked to somebody. They often produced incorrect pronunciation of the vocabulary. Therefore, they occasionally repeated the mispronunciation vocabulary. The problems they faced affected their speaking activity. Four of five students confessed that those problems become obstacle on their speaking ability because it could make them feeling insecure, less of confidence, trying to end the conversation, or change the topic immediately. Besides, one of the participants assumed that we should not think too much about mistakes when we spoke because the most important thing in communicating to people is that we can understand each other of what we wanted to convey.